Levels and Effects of Organohalogenated Contaminants on Thyroid Hormone Levels in Glaucous Gulls (Larus hyperboreus) from Kongsfjorden, Svalbard. - Haugerud, Anja Johansen (Institutt for biologi, 2011)
The glaucous gull (Larus hyperboreus) is one of the largest flying top predators in the Arctic and is exposed to rather high levels of different persistent organohalogenated contaminants (OHCs). The present study investigated whether the serum thyroid hormone (TH) levels in female glaucous gulls breeding in Kongsfjorden (79oN) may be affected by the various OHCs. A slight decrease in traditional OHCs, like polychlorinated biphenyls (PCBs) and some pesticides have been reported over the last decade, while increasing levels of new and emerging compounds like polybrominated diphenyl ethers (PBDEs) and perfluoroalkyl substances (PFASs) are detected in Arctic marine and terrestrial wildlife. Although further production of some possible endocrine disruptive chemicals have been banned by many nations, the chemicals persist, move throughout the biosphere and are potentially harmful to exposed wildlife and biota.After 35 years of contaminant research, the Svalbard glaucous gull function as a bioindicator species. Previous assessments have concluded that OHC levels were high enough to be of concern for a number of physiological effects, among them endocrine alterations. However, this is to my knowledge the first biomarker study on levels of THs in breeding glaucous gulls from Kongsfjorden. Plasma from 19 nesting female glaucous gulls was analysed for PCBs, organochlorinated pesticides (OCPs) (such as dichlorodiphenyltrichloroethane [DDT] and chlordanes) and their metabolites, PBDEs and PFASs. Total and free ranging THs were quantified using radioimmuno assay (RIA). Multivariate statistics were used to investigate the relationships between the TH levels and the explanatory variables.The PCBs represented the most pervasive compound group in the present study, as 61.3 % of the total contaminant burden in female glaucous gulls. The other contaminant groups contributed as follows: ΣDDTs (17.5 %) > ΣPFASs (14.8 %) > HCB (2.9 %) > ΣCHLs (2.7 %) > ΣPBDE (0.8 %) > ΣHCH (0.1 %). Several of the PFASs correlated ...